Some inequalities on vertex degrees, eigenvalues, and Laplacian eigenvalues of graphs - Li, Rao (Utilitas Mathematica, 2009)
Using a theorem of Hoffman and Wielandt, we present some inequalities on vertex degrees, eigenvalues, and Laplacian eigenvalues of graphs.